Basic understanding and therapeutic approaches to target toll‐like receptors in cancerous microenvironment and metastasis. Issue 5 (28th December 2017) - Khajeh Alizadeh Attar, Mojtaba; Anwar, Muhammad Ayaz; Eskian, Mahsa; Keshavarz‐Fathi, Mahsa; Choi, Sangdun; Rezaei, Nima
Abstract: Toll‐like receptors (TLRs) are transmembrane components that sense danger signals, like damage‐ and pathogen‐associated molecular pattern molecules, as receptors, and maintain homeostasis in tissues. They are mainly involved in immune system activation through a variety of mediators, which either carry out (1) elimination of pathogenic threats and redressing homeostatic imbalances or (2) contribution to the initiation and worsening of pathological conditions, including cancers. Under physiological conditions, TLRs coordinate the innate and adaptive immunity, and inhibit autoimmune disorders. In pathological conditions, such as cancer, they can present both tumor and receptor‐specific roles. Although the roles of individual TLRs in various cancers have been described, the effects of targeting TLRs to treat cancer and prevent metastasis are still controversial. A growing body of literature has suggested contribution of both activators and inhibitors of TLR signaling pathway for cancer treatment, dependent on several context‐specific factors. In short, TLRs can play dual roles with contradictory outcomes in neoplastic conditions. This hampers the development of TLR‐based therapeutic interventions. A better understanding of the interwoven TLR pathways in cancerous microenvironment is necessary to design TLR‐based therapies. In this review, we consider the molecular mechanisms of TLRs signaling and their involvement in tumor progression. Therapeutic modalities targeting TLRs for cancer treatment are discussed as well.